Pengaruh Growth Opportunity, Corporate Social Responsibility, Good Corporate Governance dan Keputusan Investasi terhadap Nilai Perusahaan (Studi Pada Perusahaan Sektor Property, Real Estate & Building Construction Periode 2013-2017) - Muhammad Fariz Wiranoto (Jurnal Ilmu Manajemen, 2021)
This study analyses influence growth opportunities, corporate social responsibility, managerial ownership, committee audit, and investment decision to the company property, real estate & buildings construction sector from 2013 to 2017. This research is quantitative, employing purposive sampling and obtaining samples from 49 companies. Technique analysis used is multiple regression by SPSS. The research results show that growth opportunities, corporate social responsibility, managerial ownership, committee audit, and investment decision have a significant influence on the company. Partial it shows that: 1) growth opportunities have a positive impact significantly on the company, based on the results of data analysis, the companies experiencing a decline and increasing growth opportunity are also proven to be followed by an increase and decrease in firm value or (PER). 2) corporate social responsibility does not have significantly on the company. Based on data analysis from 40 sample companies, only one company presents more than 50% GRI information. 3) Managerial ownership does not have significantly on the company. From the data analysis results, most companies do not have managerial ownership companies. 4) The audit committee has no significant effect on the company's value because an audit committee in the company is seen only as a fulfilment of the government's regulatory obligations. The audit committee has not carried out its obligations in a manner maximum. 5) Investment decisions significantly do not affect the company's value because most companies have not implemented meaningful investment decisions, as evidenced by a TAG value of less than 1.